Pengembangan Kawasan Kampung Pelangi Semarang: Persepsi dan Dukungan Masyarakat - Aryaningtyas, Aurilia Triani; Aprilliyani, Renny; Soehari, Hartoyo (Jurnal Master Pariwisata (JUMPA), 2021)
This study attempts to make a little contribution to the sustainable development of tourism by examining the residents’ perceptions and support on the impact of the development of the Rainbow Village area as a tourist attraction in Semarang. Data were collected by means of a questionnaire. Based on 100 respondents surveyed, the findings show that the majority of respondents were male, aged between 36-45 years, were a native, who were born and lived in Wonosari village for more than 15 years. Overall, respondents viewed tourism positively and would support this development, because they consider the development of rainbow Village to contribute economically as well as socio-culture in Kampung Wonosari Semarang. They were generally in favor of development of rainbow Village that contributes economically and socio-culturally to Wonosari village. They were, however, slightly ambivalent to environmental impacts of tourism. Implications, policy recommendations and limitations of study are presented in the conclusion. Keywords: perception, support, residents, development, rainbow village